NANO-BIOPOLYMERS IN DENTISTRY - Supriya Nambiar , Dilip G. Naik, Dhruv Ahuja, Shantam Gupta, Carol Lobo (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Biopolymers at nanoscale are of immense value for its medical and dental applications. Chitosan is abundant in nature and chitosan nanoparticles have been widely used for biomedical applications because of its antibacterial and antimicrobial properties. Similarly there are other bio polymers widely used in the medical and health care sector.This review attempts to provide a comprehensive insight on the applications of Nanobiopolymers in orthodontics, its significance and uses.